KESESUAIAN DAN DAYA DUKUNG WISATA PANTAI KATEGORI REKREASI DI PANTAI TETE, DESA BONEPUTE, KABUPATEN BONE - Beddu Tang; Asmidar Asmidar (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
This study aims to determine the suitability and carrying capacity of the Tete Beach tourism area in Bonepute Village, Tonra District, Bone Regency, as a recreational beach category tourism. The study was conducted in October 2019 to March 2020. The method used was a survey method with primary and secondary data collection through observation techniques. Primary data include data on the aquatic environment, the physical environment of the coast, the area of ​​the area used for beach tourism activities, and the time used by tourists in the coastal zone. Data analysis uses the tourism suitability index and the carrying capacity of the coastal area. The suitability value of Tete beach tourism based on the analysis results obtained on average is 95% (very appropriate / S1). The carrying capacity of the area obtained is 300 people/day for recreational tourism activities, and 450 people/day for beach sports activities. Based on this value, the Tete coastal area has a large capacity for recreational activities and beach sports.